2022
DOI: 10.1186/s10194-021-01381-w
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in pain processing circuitries in episodic migraine

Abstract: Background The precise underlying mechanisms of migraine remain unknown. Although we have previously shown acute orofacial pain evoked changes within the brainstem of individuals with migraine, we do not know if these brainstem alterations are driven by changes in higher cortical regions. The aim of this investigation is to extend our previous investigation to determine if higher brain centers display altered activation patterns and connectivity in migraineurs during acute orofacial noxious sti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Thus, migraine is regarded as a “connectopathy” rather than a disease arising from dysfunctioning of specific areas of the brain. Interestingly, the same technique also showed a heightened connection between sensory areas and areas regulating affective processes including the limbic system [ 25 28 ], which is implied in pain processing and in the regulation of emotional life. This may explain migraineurs’ susceptibility to external triggers causing sensory overload; those triggers may modify brain circuits functioning [ 29 31 ].…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…Thus, migraine is regarded as a “connectopathy” rather than a disease arising from dysfunctioning of specific areas of the brain. Interestingly, the same technique also showed a heightened connection between sensory areas and areas regulating affective processes including the limbic system [ 25 28 ], which is implied in pain processing and in the regulation of emotional life. This may explain migraineurs’ susceptibility to external triggers causing sensory overload; those triggers may modify brain circuits functioning [ 29 31 ].…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…Previous study suggested that the etiology of migraine is dysfunction of the pain regulation pathway ( 36 ), the PET study by Lorenz et al ( 37 ) found that substantial prefrontal cortex activation during heat stimuli on capsaicin-treated skin. Meanwhile, the current fMRI study by Mungoven et al ( 38 ) found that reduced whole scan the dorsolateral prefrontal cortex (DLPFC) connectivity with cortical/subcortical and brainstem regions involved in pain modulation was demonstrated in migraineurs. Furthermore, the functional connection between brain regions that play an important role in regulating pain is significantly weakened, suggesting that migraine could be relieved if the dysfunction of the pain regulation pathway is improved ( 39 ).…”
Section: Discussionmentioning
confidence: 83%
“…Numerous rs-fMRI studies have been conducted to elucidate the physiological underpinnings of migraine (Messina R et al, 2022). In particula, aberrant descending pain modulatory pathway prior to the migraine attack, abnormal thalamo-cortical and frontoparietal pathways involved in pain transmission and modulation have been observed in migraine individuals Nie W et al, 2021;Lim M et al, 2021;Mungoven TJ et al, 2022) In this study, we posit a potential correlation between RLS and functional alterations in integration and segregation in individuals with migraines. To examine this hypothesis, the study meticulously explores RLS-associated brain functional aberrations in migraine individuals with and without RLS The overarching goal is to unravel the underlying connection between RLS and migraines, contributing to a comprehensive understanding of this intricate interplay.…”
Section: Introductionmentioning
confidence: 86%